STRATEGI MENJAGA KESEIMBANGAN EKOSISTEM LAUT DENGAN MEMANFAATKAN RECYCLE ECONOMY UNTUK MENGHADAPI ANCAMAN EL NINO - Wahyudi, Ahmad Shohibboniawan; Aditya Rahman; Suwito, Suwito (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Human dependence on natural resources, especially in the Blue Economy sector or marine ecosystems, has led to a dominant role in ecosystem management. The El Niño phenomenon is a serious challenge that can disrupt marine ecosystems and sustainable economies. This effort aims to reduce the negative impact of El Nino on marine ecosystems, by recycling the economy from wastes in the sea. This research uses a descriptive qualitative approach to reduce the negative impact of El Niño on marine ecosystems through recycling of marine waste, creating a sustainable solution for economic growth and environmental sustainability. SWOT analysis and complex systems theory highlighted several potential strategies to stabilize the marine ecosystem, address the threat of El Niño, and boost the economy. The implementation of these strategies has a positive impact on the sustainability of the marine ecosystem and sustainable economic growth.